1986
DOI: 10.3758/bf03207584
|View full text |Cite
|
Sign up to set email alerts
|

Dichoptic temporal frequency differences do not lead to binocular rivalry

Abstract: The influence of temporal modulation on binocular rivalry was examined in two ways. First, an uncontoured field viewed by one eye had its luminance sinusoidally modulated at 4 Hz (fullfield flicker). The other eye viewed a similar field that flickered at different temporal frequencies ranging from .5 to 16 Hz. Second, orthogonal sinusoidal dichoptic gratings were phase shifted so as to duplicate the range of temporal-frequency disparities presented with full-field flicker. Three subjects recorded exclusive vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
3
15
1
Order By: Relevance
“…An ideal stimulus would contain temporal modulations and no form conflict. The full-field flicker stimulus of O'shea and Blake (1986) comes close to this, but it contains no contrast—the primary attribute driving the response level of early visual neurons. In the present study, we will examine whether interocular temporal differences elicit rivalry using a novel stimulus: a random dynamic-noise sequence that is temporally filtered into narrow temporal pass-bands.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…An ideal stimulus would contain temporal modulations and no form conflict. The full-field flicker stimulus of O'shea and Blake (1986) comes close to this, but it contains no contrast—the primary attribute driving the response level of early visual neurons. In the present study, we will examine whether interocular temporal differences elicit rivalry using a novel stimulus: a random dynamic-noise sequence that is temporally filtered into narrow temporal pass-bands.…”
Section: Introductionmentioning
confidence: 83%
“…Testing the aftereffects with a binocularly-viewed dynamic test pattern did elicit rivalry alternations. Against this, however, another study using full-field flicker found that different temporal modulation rates in each eye failed to elicit any rivalry at all (O'shea and Blake, 1986). …”
Section: Introductionmentioning
confidence: 99%
“…We know, for example, that interocular differences in rate of luminance flicker do not produce binocular rivalry alternations in the absence of form differences (O’Shea and Blake, 1986). We also know that the perceived direction of motion of a pattern dominant during rivalry can be influenced by the motion direction of the suppressed pattern, implying that motion information from the suppressed eye remains partially effective (Andrews and Blakemore, 1999, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a plethora of studies on the spatial aspects of rivalry, its temporal behavior been explored less extensively. When stimuli are defined by spatial form but also have a temporal component, rivalry is usually possible provided the temporal frequencies are similar (42,43). Over a limited range, faster stimuli will dominate over slow or static stimuli (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%